2022
DOI: 10.1177/22799036221103382
|View full text |Cite
|
Sign up to set email alerts
|

Perceived severity of COVID-19, social support, and pandemic-related stress associated with lifestyle changes among undergraduate students in Indonesia

Abstract: Introduction: COVID-19 affects lifestyles, including those of undergraduate students who are one of the most vulnerable populations. This study aimed to describe changes in lifestyle-related behaviors and assess the correlation between the perceived risk of COVID-19, social support, perceived stress, and lifestyle changes among undergraduate students during the pandemic. Design and methods: A total of 547 students from 32 provinces in Indonesia completed online questionnaires comprising four measures: perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
(53 reference statements)
1
1
0
Order By: Relevance
“…They engage in behaviors that are effective in the short term to adapt to stress (like smoking and drinking), But they are not considered healthy at all [ 36 ]. The current result demonstrated that a healthy lifestyle predicts a lower level of covid-19 related stress, which is consistent with the result of previous research conducted with Indonesian participants [ 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…They engage in behaviors that are effective in the short term to adapt to stress (like smoking and drinking), But they are not considered healthy at all [ 36 ]. The current result demonstrated that a healthy lifestyle predicts a lower level of covid-19 related stress, which is consistent with the result of previous research conducted with Indonesian participants [ 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…The results on overall patterns and seasonal changes in concerns (RQ1) indicated that the concerns in different domains of people’s lives were similar over the period under consideration, but with some variations. Social concerns took on a special position in comparison, which underlines the influence of the pandemic on personal relationships, as already demonstrated in other studies ( 4 , 43 ). Although the differences are within the range of less than one scale point, they are meaningful in view of the sample size and the observation over a period of 3 years.…”
Section: Discussionsupporting
confidence: 70%
“…Not only have people been physically affected by the disease itself caused by SARS-CoV-2, but there have also been problems with mental health as a result of measures taken by governments ( 1 , 2 ). Other affected areas relate to financial conditions, for example due to the loss of jobs ( 3 ), or social issues due to fewer and altered opportunities for interpersonal interaction ( 4 ). Individuals form their own opinions on these topics and such perceptions can have an impact on behavior with regard to compliance with measures ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Favorable social support can make individuals feel higher self-efficacy, self-esteem, 12 subjective well-being, 13 psychological resilience, 14 life satisfaction, 15 level of hope, 16 and career adaptability, and can enable individuals to have a healthier lifestyle. 17 Social support is an important factor affecting individual prosocial behavior, and has a significant positive correlation with altruistic behavior, 18 thereby playing an important role in maintaining and promoting physical and mental health. Another researcher found that "The COVID-19 pandemic has highlighted the importance of social support for everyone".…”
mentioning
confidence: 99%